2016
DOI: 10.1080/13814788.2016.1177507
|View full text |Cite
|
Sign up to set email alerts
|

How do Dutch GPs address work-related problems? A focus group study

Abstract: The participating GPs seemed well aware of the relation between work and health but need more knowledge, communication skills and better cooperation with occupational physicians to manage work-related problems. [Box: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…It covered six topics: (1) the connection between work and health; (2) usual care for WRPs and ways to improve it; (3) legislation regarding absenteeism and collaboration with OP; (4) gender aspects of work and WRPs; (5) activating care for patients with work-related distress; (6) registration of occupation and WRPs in the electronic medical record (EMR). The programme was based on the results of a focus group study, in which we found that lack of knowledge and counselling skills were barriers for GPs to identify and address WRPs proactively [ 22 ]. The programme ended with instructions about the recruitment of patients for the trial.…”
Section: Methodsmentioning
confidence: 99%
“…It covered six topics: (1) the connection between work and health; (2) usual care for WRPs and ways to improve it; (3) legislation regarding absenteeism and collaboration with OP; (4) gender aspects of work and WRPs; (5) activating care for patients with work-related distress; (6) registration of occupation and WRPs in the electronic medical record (EMR). The programme was based on the results of a focus group study, in which we found that lack of knowledge and counselling skills were barriers for GPs to identify and address WRPs proactively [ 22 ]. The programme ended with instructions about the recruitment of patients for the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Although most health professionals, including physical therapists, acknowledge the importance of their patients' work, occupation and the ability to work, these topics are often not addressed within regular Dutch healthcare [14][15][16][17][18]. Recent qualitative research in the Netherlands found that although a patient's work is considered important, physical therapists take work participation insufficiently into account as a determining factor in the treatment of patients with MSDs.…”
Section: Introductionmentioning
confidence: 99%
“…These issues were also seen in qualitative research conducted among general practitioners in the Netherlands which found that general practitioners seemed well aware of the relationship between work and health but needed more knowledge, communication skills and better cooperation with occupational physicians to manage workrelated problems. Participants reported that they lacked the knowledge to advise patients specifically concerning their work environment [16].…”
Section: Introductionmentioning
confidence: 99%
“… 3 33 Yet GPs often have difficulties managing their patients’ work-related mental health problems, as they often lack negotiation strategies regarding sick leave, communication skills and cooperation with occupational physicians. 34 GPs encounter a variety of workers with systematic, unsystematic or non-existing occupational health services at their workplace. A better understanding of work-related factors associated with individuals’ mental health is important to help GPs consider specific actions.…”
Section: Introductionmentioning
confidence: 99%